Increased hepatic lipogenesis but decreased expression of lipogenic gene in adipose tissue in human obesity - Diraison, Frederique; Dusserre, Eric; Vidal, Hubert; Sothier, Monique; Beylot, Michel (American journal of physiology: endocrinology and metabolism, 2002)
Institut National de la Santé et de la Recherche Médicale Unité 1  499 and 2  449, Faculté RTH Laennec, 69008 Lyon, France; and 3  Centre de Recherche en Nutrition Humaine, Hôpital E. Herriot, 69003 Lyon, France To determine whether increased lipogenesis contributes to human obesity, we measured (postabsorptive state), in lean and obese subjects, lipid synthesis (deuterated water method) and the mRNA concentration (RT-competitive PCR) in subcutaneous adipose tissue of fatty acid synthase (FAS) and sterol regulatory element-binding protein (SREBP)-1c. Before energy restriction, obese subjects had an increased contribution of hepatic lipogenesis to the circulating triglyceride pool (14.5 ± 1.3 vs. 7.5 ± 1.9%, P  < 0.01) without enhancement of cholesterol synthesis. This increased hepatic lipogenesis represented an excess of 2-5 g/day of triglycerides, which would represent 0.7-1.8 kg on a yearly basis. The lipogenic capacity of adipose tissue appeared, on the contrary, decreased with lower FAS mRNA levels ( P  < 0.01) and a trend for decreased SREBP-1c mRNA ( P  = 0.06). Energy restriction in obese patients decreased plama insulin ( P  < 0.05) and leptin ( P  < 0.05) and normalized hepatic lipogenesis. FAS mRNA levels were unchanged, whereas SREBP-1c increased. In conclusion, subjects with established obesity have an increased hepatic lipogenesis that could contribute to their excessive fat mass but no evidence for an increased lipogenic capacity of adipose tissue. fatty acid synthase; sterol regulatory element-binding protein-1c; stable isotope; messenger ribonucleic acid; lipids